O PANTANAL DE AQUIDAUANA NA PONTA DOS DEDOS: AUXILIANDO A ESCOLARIZAÇÃO GEOGRÁFICA DE ALUNOS DEFICIENTES VISUAIS. - LUANA REDRANG GROSSI (2021)
The present work has the objective of knowing the Brazilian educational public policy directed to the visually impaired student and to elaborate pedagogical resources to facilitate the teaching of Geography of Pantanal biome to blind and low vision students. The reflections presented in this work were developed from three methodological procedures: documentary and bibliographical research and interviews with social actors directly involved in the process. A historical survey of the legal instruments referring to special education in the national, state (Mato Grosso do Sul) and municipal (Aquidauana) spheres was carried out, emphasizing the public policies referring to people with visual impairment and interviews with elementary school teachers from the public school system who taught classes to a blind student. The results point to the possibility of working the Pantanal biome in an inclusive way, bringing its uniqueness, physical and environmental aspects, contributing to a better learning of blind students and students with low vision in relation to the subject of Geography from the use of pedagogical resources facilitators regarding the Pantanal biome. Keywords: visual disability, inclusion, Pantanal biome, pedagogical resources, teaching of Geography.